Pelaksanaan pembelajaran abad ke-21 (PAK21) dalam kalangan guru-guru berdasarkan model TPACK - Mohd Fathim, Mohd Talib (2022)
PAK21 was introduced in line with the Malaysia Education Development Plan 2013-2025 (PPPM) by KPM (2013). TPACK comprises seven components, namely technological knowledge (TK), pedagogical knowledge (PK), content knowledge (CK), technological pedagogical knowledge (TPK), technological content knowledge (TCK), pedagogical content knowledge (PCK) and technological pedagogical content knowledge (TPACK). TPACK21 is the combination of TPACK and PAK21. This study was conducted to identify the level of technological pedagogical content knowledge in 21st-century learning (TPACK21) of teachers as well as the level of knowledge for other components of TPACK, the relationship between TPACK and TPACK21 and the influence of the independent variables on TPACK21. Technological pedagogical content knowledge (TPACK) and 21st-century learning (PAK21) are the main foundations for this study. The study design was quantitative. One hundred seventy-five respondents from boarding school teachers (SBP) throughout Kedah were involved. This study adapted the instruments from the Measuring 21st Century Teaching and Learning and Technological Pedagogical Content Knowledge (TPACK). Reliability tests were performed by researcher as well as validity tests reviewed by three experts. The findings show that all components of TPACK, namely PK, CK, TPK, TCK and PCK and TPACK21, have high levels. Meanwhile, TK has a moderately high level, and the highest level is CK. All components of the independent variables show significantly positive relationships to TPACK21. The highest correlation is between TPK and TPACK21, while the lowest is CK and TPACK21. The results of the multiple regression test show that the three independent variables which influence TPACK21 are TPK, TCK and PCK. The primary influence of this study is TPK. TPACK21 needs to be mastered by teachers, especially technological knowledge, to impact national education effectively.